(untitled) (Agora for Physical Education and Sport, 2021)
The research compares the quality of life between military and university students. Cross-sectional study with a descriptive design, with 206 physically active male participants, 101 university students deported and 105 young soldiers with a mean age of 19.4 years. The necessary care for the IPAQ, cropped version to select participants with the level of “active” physical activity and Whoqol-bref to identify the level of quality of life. Response data were grouped into 4 different domains: Physical, Psychological, Social Relations and Environment; The results showed a better perception of quality of life and risk factors such as nutritional status and tobacco use among young soldiers in relation to university students.